Illumina Sequencing Reveals the First Near-Complete Genome Sequence of Ugandan Passiflora Virus - Mbeyagala, E.K.; Maina, S.; Macharia, M.W.; Mukasa, S.B.; Holton, T.A. (American Society for Microbiology, 2019)
Here, we present the first near-complete genome of Ugandan Passiflora virus (UPV) sequenced from a symptomatic sample of KH7 passion fruit (Passiflora edulis Sims) variety. UPV had limited amino acid identity with other potyviruses known to cause passion fruit woodiness disease (PWD).